Validation of flavivirus infectious clones carrying fluorescent markers for antiviral drug screening and replication studies - Cherkashchenko, Liubov; Gros, Nathalie; Trausch, Alice; Neyret, Aymeric; Hénaut, Mathilde; Dubois, Gregor; Villeneuve, Matthieu; Chable-Bessia, Christine; Lyonnais, Sébastien; Merits, Andres; Muriaux, Delphine (Frontiers in Microbiology, 2023)
Flaviviruses have emerged as major arthropod-transmitted pathogens and represent an increasing public health problem worldwide. High-throughput screening can be facilitated using viruses that easily express detectable marker proteins. Therefore, developing molecular tools, such as reporter-carrying versions of flaviviruses, for studying viral replication and screening antiviral compounds represents a top priority. However, the engineering of flaviviruses carrying either fluorescent or luminescent reporters remains challenging due to the genetic instability caused by marker insertion; therefore, new approaches to overcome these limitations are needed. Here, we describe reverse genetic methods that include the design and validation of infectious clones of Zika, Kunjin, and Dengue viruses harboring different reporter genes for infection, rescue, imaging, and morphology using super-resolution microscopy. It was observed that different flavivirus constructs with identical designs displayed strikingly different genetic stabilities, and corresponding virions resembled wild-type virus particles in shape and size. A successful strategy was assessed to increase the stability of rescued reporter virus and permit antiviral drug screening based on quantitative automated fluorescence microscopy and replication studies.